Aplikasi Pencarian Pet Hotel di Surabaya dengan Menggunakan Metode Simple Additive Weighting - Michael Gozali; Alexander Setiawan; Anita Nathania Purbowo (Jurnal Infra, 2019)
Pet hotel is a pet care service where pet owners can leave their pets for several days. In Surabaya, finding an ideal place for pets is quite a difficult task. Because not everyone is willing and able to accept and take care a pet. In addition, there’re also many pet shops in Surabaya that don’t provide pet hotel service, so finding a pet hotel in surabaya is a real challenge. Another thing that also makes it difficult to find a pet hotel is the lack of information about pet shops that have pet hotel services. Most of the pet shops in Surabaya still rely on brochures and word-of-mouth method to spread information about their businesses. This of course will make it difficult for pet owners to find a pet hotel. In this thesis an Android based application for searching pet hotel will be craeted by implementing Simple Additive Weighting Method in the application system. The implentation of SAW method is aimed to find the best alternative based on the criteria determined by survey. The criteria used included number of staff, the capacity of animal that can be accomodated, the type of location, number of facilites, facility price, and animal price. The searching process is done with the user giving weight for each criteria then SAW will determine which pet hotel has the highest priority, namely the pet hotel that best suits the user’s preference.The final result of this thesis is an application that can help pet owners find pet hotels in Surabaya with preferences that best suit the user’s wishes based on the Simple Additive Weighting method. The result of the Simple Additve Weighting testing conducted show that the SAW calculations performed in the applcation have been able to provide the same result as the calculations done manually.